2010
DOI: 10.1016/s0377-1237(10)80083-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Nebulised Salbutamol and L-epinephrine in First Time Wheezy Children

Abstract: Background: Salbutamol is the standard recommendation in bronchial asthma. However, the use of bronchodilators in wheeze associated respiratory infections including bronchiolitis continues to be controversial. The aim of this study was to compare the efficacy of nebulised salbutamol versus epinephrine in 'first time' wheezy children using clinical parameters and airway resistance. Methods: Sixty children between two months to 60 months were recruited, 30 in each treatment group. Children received periodic (0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Variables and their two levels are presented in Table 2 . The 2 3 full factorial design is used to optimize the formulation variables with basic requirement of understanding interaction of independent variables. Linear, cross-product contribution (2FI), quadratic, and cubic models were generated for the responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables and their two levels are presented in Table 2 . The 2 3 full factorial design is used to optimize the formulation variables with basic requirement of understanding interaction of independent variables. Linear, cross-product contribution (2FI), quadratic, and cubic models were generated for the responses.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Asthma may also be classified as atopic (extrinsic) or nonatopic (intrinsic), where atopy refers to a predisposition toward developing type 1 hypersensitivity reactions. 2 , 3 Asthma is the clinical condition that may occur in adult and pediatric patients. For some children with asthma, their first asthmatic experience can be frightening – heavy wheezing, a tight chest, and shortness of breath can quickly catch their active, young bodies off-guard.…”
Section: Introductionmentioning
confidence: 99%
“…P opula on studies have shown that approximately one in three children has at least one episode of wheezing prior to their third birthday, and the cumula ve prevalence of wheeze is almost 50% at the age of six years 1 . Despite its high prevalence, there is a lack of evidence regarding the pathophysiology and treatment of fi rst episode of wheeze 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high prevalence, there is a lack of evidence regarding the pathophysiology and treatment of fi rst episode of wheeze 1 . WHO es mates that in 2001, iron defi ciency anaemia (IDA) resulted in 273,000 deaths: 45% in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%